Consumer Search and Double Marginalization - Janssen, Maarten; Shelegia, Sandro (American Economic Review, 2015)
The well-known double marginalization problem understates the inefficiencies arising from vertical relations in consumer search markets where consumers are uninformed about the wholesale prices charged by manufacturers to retailers. Consumer search provides a monopoly manufacturer with an additional incentive to increase its price, worsening the double marginalization problem and lowering the manufacturer's profits. Nevertheless, manufacturers in more competitive wholesale markets may not have an incentive to reveal their prices to consumers. We show that retail prices decrease in search cost, and so both industry profits and consumer surplus increase in search cost. (JEL D11, D42, D83, L12, L25, L60, L81)